2019
DOI: 10.1016/j.pepi.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the Holocene palaeointensity database in Central America: Impact on geomagnetic modelling

Abstract: Thanks to its rich archaeological heritage, Central America is a key region to recover the past secular variation of the geomagnetic field. This article presents 13 new palaeointensity data on Epiclassic (650-900 CE) pottery sherds from Central Mexico. Archaeointensities were determined using the Thellier-Thellier protocol with anisotropy and cooling rate corrections. Average results between 25 and 42 µT reveals a fast secular variation in the second half of the first millennium CE but are not in agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Data were retrieved from GEOMAGIA50 (Brown et al, 2021) Open (full) circles on Zijderveld plots correspond to a vertical (horizontal) plane projection, respectively. and from regional compilations (Hervé, Perrin, Alva-Valdivia, Tchibinda Madingou, et al, 2019;Jones et al, 2020Jones et al, , 2021Mahgoub, Juárez-Arriaga, Böhnel, Manzanilla, & Cyphers, 2019;Soler-Arechalde et al, 2019). Data were relocated to Casas de Fuego via the Virtual Geomagnetic Pole (VGP) and the Virtual Axial Dipole Moment (VADM) assumptions for directions and intensities respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were retrieved from GEOMAGIA50 (Brown et al, 2021) Open (full) circles on Zijderveld plots correspond to a vertical (horizontal) plane projection, respectively. and from regional compilations (Hervé, Perrin, Alva-Valdivia, Tchibinda Madingou, et al, 2019;Jones et al, 2020Jones et al, , 2021Mahgoub, Juárez-Arriaga, Böhnel, Manzanilla, & Cyphers, 2019;Soler-Arechalde et al, 2019). Data were relocated to Casas de Fuego via the Virtual Geomagnetic Pole (VGP) and the Virtual Axial Dipole Moment (VADM) assumptions for directions and intensities respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the last 2 kyrs, 192 intensity averages were found within 2,000 km from Casas de Fuego: 141 from Mexico (see Alva-Valdivia et al, 2021;Garcia et al, 2021;Hervé, Perrin, Alva-Valdivia, Tchibinda Madingou, et al, 2019;Mahgoub, Juárez-Arriaga, Böhnel, Manzanilla, & Cyphers, 2019) and 51 from Western North America (e.g., Bowles et al, 2002;Champion, 1980;Jones et al, 2020;Sternberg, 1982). Archeological baked clays constitute 80% of the data set.…”
Section: Comparison With Intensity Data and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRM intensity also depends on the cooling duration, and many archaeointensity studies on baked clays have demonstrated the necessity to correct this cooling rate effect, when the duration of the initial and laboratory cooling is significantly different (e.g., Fox & Aitken, ; Hervé et al, ). In this study, the cooling of the specimens in the laboratory furnace lasted about 30 min that is much faster than the archaeological cooling.…”
Section: Archaeomagnetic Experimentsmentioning
confidence: 99%
“…If we cannot totally discard an effect of this possible underestimation of the archaeological cooling on the archaeointensity determinations, it was shown that the TRM intensity increases with the cooling duration following a logarithmic trend (e.g., Genevey et al, ; Halgedahl et al, ). Hervé, Perrin, et al () demonstrated that such imprecision on the cooling estimation does not result in a significant inaccuracy of the average archaeointensity. Furthermore, much slower values of cooling rate are not expected at this archaeological period.…”
Section: Archaeomagnetic Experimentsmentioning
confidence: 99%